Managing insulin therapy during exercise inType 1 diabetes mellitus - Toni, Sonia; Reali, Francesca; Barni, Federica; Lenzi, Lorenzo; Festini, Filippo (Acta Biomedica Atenei Parmensis, 2006)
Background: Exercise is integral to the life of T1DM subjects. Several factors influence the metabolic response to exercise in these patients. Despite physical and psychological benefits of exercise, its hypoand hyperglycemic effects may cause discouragement from participation in sports and games. Aim: To use existing evidence from literature to provide practical indications for the management of insulin therapy in subjects with T1DM who practice sports or physical activities. Methods: Bibliographic research was performed on PubMed and the main Systematic Review and Guidelines database were also searched. Results: Existing guidelines are useful but the exact adjustments of insulin dose must be made on an individual basis and these adjustments can be made only by “trial and error” approach. Conclusions:These clinical indications may be a starting point from which health care providers can find practical advices for each patient.